Marxist Feminism as Portrayed by The Main Characters in The Movie Hidden Figures - Pinontoan, Marcela; Ni Made Suwari Antari; Putu Ayu Asty Senja Pratiwi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This article examined Marxist Feminism as portrayed by the main characters in the film Hidden Figures. The researcher aimed to find the violation of Marxist Feminism in the movie and to identify personality traits of the main characters in facing daily discrimination in relation to Marxist Feminism violation. This research utilized the documentation method to collect data and the descriptive-qualitative method to present as well as explain how the data from the movie supports the objective of this study. In addition, Hartmann's Marxist Feminism theory (1979) and Murphy's characterization theory (1972) are used to analyze the data in this research. The findings of this research showed that the main characters in this film successfully coped with all of their problems caused by Marxist feminism stereotypes and violations with a righteous attitude. The three main characters are described as strong-willed women, which helps them deal with the daily discrimination that colored women faced at the time. Being determined, dedicated, outspoken, smart, and decisive helps them deal with everyday problems.